Increased Activity of Vitamin K-Dependent Clotting Factors in Human Hyperlipoproteinaemia – Association with Cholesterol and Triglyceride Levels - Constantino, M; Merskey, C; Kudzma, D. J; Zucker, M. B (Thrombosis and Haemostasis, 1977)
Levels of blood coagulation factors, cholesterol and triglyceride were measured in human plasma. Prothrombin was significantly elevated in type Ha hyperlipidaemia; prothrombin and factors VII, IX and X in type lib; and prothrombin and factors VII and IX in type V. Multiple regression analysis showed significant correlation between the levels of these plasma lipids and the vitamin K-dependent clotting factors (prothrombin, factors VII, IX and X). Higher cholesterol levels were associated with higher levels of prothrombin and factor X while higher triglyceride levels were associated with higher levels of these as well as factors VII and IX. Prothrombin showed a significant cholesterol-triglyceride interaction in that higher cholesterol levels were associated with higher prothrombin levels at all levels of triglyceride, with the most marked effects in subjects with higher triglyceride levels. Higher prothrombin levels were noted in subjects with high or moderately elevated (but not low) cholesterol levels. Ultracentrifugation of plasma in a density of 1.21 showed activity for prothrombin and factors VII and X only in the lipoprotein-free subnatant fraction. Thus, a true increase in clotting factor protein was probably present. The significance of the correlation between levels of vitamin K-dependent clotting factors and plasma lipids remains to be determined.